2016
DOI: 10.1016/j.expneurol.2016.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rapamycin on status epilepticus induced hippocampal pathology and weight gain

Abstract: Growing evidence implicates the dentate gyrus in temporal lobe epilepsy (TLE). Dentate granule cells limit the amount of excitatory signaling through the hippocampus and exhibit striking neuroplastic changes that may impair this function during epileptogenesis. Furthermore, aberrant integration of newly-generated granule cells underlies the majority of dentate restructuring. Recently, attention has focused on the mammalian target of rapamycin (mTOR) signaling pathway as a potential mediator of epileptogenic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 121 publications
(159 reference statements)
2
26
0
Order By: Relevance
“…Noteworthy, rapamycin can also suppress the sprouting of inhibitory hilar neurons axons, which may possibly have negative net effects on hippocampal hyperexcitability. 59 Besides inhibiting mossy fiber sprouting, rapamycin has little or no effect on other SE-induced GCL phenotypes, including basal dendrite formation and ectopic granule cell generation, 57,60,61 which may explain the negative results on seizure prevention in some models. 57,60 Another potential mechanism by which increased activation of mTORC1 within the temporal lobe structures may promote epileptogenesis is by altering expression and function of neurotransmitter receptors and ion channels, given that previous studies have demonstrated that rapamycin treatment prevented seizure-induced enhancement of glutamatergic function 4 and reversed several ion channels abnormalities in hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, rapamycin can also suppress the sprouting of inhibitory hilar neurons axons, which may possibly have negative net effects on hippocampal hyperexcitability. 59 Besides inhibiting mossy fiber sprouting, rapamycin has little or no effect on other SE-induced GCL phenotypes, including basal dendrite formation and ectopic granule cell generation, 57,60,61 which may explain the negative results on seizure prevention in some models. 57,60 Another potential mechanism by which increased activation of mTORC1 within the temporal lobe structures may promote epileptogenesis is by altering expression and function of neurotransmitter receptors and ion channels, given that previous studies have demonstrated that rapamycin treatment prevented seizure-induced enhancement of glutamatergic function 4 and reversed several ion channels abnormalities in hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Increased weight gain has been observed in the systemic pilocarpine mouse and rat models of TLE. 12,26 In one study examining the intrahippocampal KA female rat model, increased food intake and body weight gain were observed only when both ventral and dorsal hippocampus was injected. 27 In our study, the KA was injected only to the right dorsal hippocampus of the mice.…”
Section: Ka-treated Mice Display Increased Weight Gainmentioning
confidence: 99%
“…basal dendrites, Pun et al, 2012). Moreover, mTOR signaling is increased during epileptogenesis (Hester et al, 2016; Zeng et al, 2009), and blocking mTOR has anti-epileptogenic properties (Ljungberg et al, 2009; Wong, 2013). PTEN knockout mice developed a severe epilepsy syndrome, exhibiting both hippocampal and cortical seizures in 24/7 EEG recordings -- supporting the hypothesis that abnormal granule cells can initiate temporal lobe epileptogenesis.…”
Section: Introductionmentioning
confidence: 99%